TINJAUAN PEMENUHAN ASAS-ASAS UMUM PEMERINTAHAN YANG BAIK TERHADAP PENGATURAN JANGKA WAKTU PEMERIKSAAN PAJAK - Muhammad Wahyudi (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2026)
This study aims to analyze the fulfillment of the General Principles of Good Governance (AUPB) regarding the regulation of tax audit timeframes as stipulated in the Minister of Finance Regulation Number 15 of 2025 concerning Tax Audits. The regulation of tax audit timeframes is an important instrument in tax administration law because it is directly related to legal certainty, protection of taxpayer rights, and limitations on the authority of tax authorities. In practice, although the regulation has set a clear audit timeframe, its implementation still raises debate, especially when the audit exceeds the specified timeframe but is still considered valid by the court decision. The research method used is normative juridical legal research with a statutory and conceptual approach. The data used are primary, secondary, and tertiary legal materials obtained through literature studies and analyzed qualitatively. The results of the study indicate that normatively the regulation of tax audit timeframes in PMK Number 15 of 2025 has reflected the principles of AUPB, particularly the principles of legal certainty, accountability, openness, professionalism, and proportionality. However, in practice, the application of audit timeframes has not been fully consistent with these principles. The Supreme Court's decision permitting audits to extend beyond the time limit demonstrates that procedural compliance is often disregarded in pursuit of material tax truth. This situation creates legal uncertainty for taxpayers and demonstrates that the AUPB has not yet fully functioned as a binding standard of review in tax audit practice. Therefore, strengthening regulations that emphasize the legal consequences of exceeding the audit time limit is needed, so that the time limit truly functions as a limit on administrative authority that provides legal protection for taxpayers and strengthens good governance in the tax sector.